THU0330 Damage in juvenile-onset systemic lupus erythematosus. (23rd January 2014) - Costa Reis, P.; Isgro, J.; Nativ, S.; Yildirim-Toruner, C.; Starr, A.; Imundo, L.; Eichenfield, A.
Abstract : Background: Children and adolescents with juvenile-onset systemic lupus erythematosus (jSLE) face considerable morbidity due to sequelae of disease activity, comorbidities and adverse effects of treatment. In order to improve the management of these patients, it is essential to better understand the risk factors associated with the development of permanent damage. Objectives: The main goals of this study were to determine the prevalence of organ damage among children with jSLE and to identify risk factors for damage. Methods: This was a retrospective chart review of the clinical courses of jSLE patients followed at MSCHONY/CUMC, from the time of diagnosis or first encounter until December 2009 or loss to follow-up. All patients were diagnosed before the age of 18, had a disease duration ≥6 months and were followed during the period 2007-2009. Disease activity (SLEDAI) at diagnosis and Systemic Lupus International Collaborating Clinics (SLICC) Damage Index (SDI) at the conclusion of the study were evaluated. Major infections were identified, defined as those that required treatment with parenteral antimicrobial agents or necessitated a course of antibiotics for more than one week. Chi-square/Fisher's exact test and t-test were used to analyze categorical and continuous data, respectively. Results: There were 120 children and adolescents with SLE: 93 female/27 male (F/M: 3.4/1), 61 Hispanic (51%) and 34 African-American (28%). The majority (53%) were diagnosed between the ages of 10-15 years. Mean duration of follow-up was 4.7±3.2 years. Mean SLEDAI at diagnosis was 9.6±6.5. Lupus nephritis affected 59 patients (49%). Neuropsychiatric manifestations (NPSLE) occurred in 15 children (12%). Mycophenolate mofetil (MMF) was used in 56% of the patients, cyclophosphamide in 37% and rituximab in 6%. The mean cumulative prednisone dose was 12g. There were 101 major infections affecting 44 patients (37%), the most common being skin infections (19), pneumonias (17), urinary tract infections with fever (14), sepsis (9), and herpes zoster (8). During the study 2 patients died due to disease-associated comorbidities. Damage (SDI ≥1) was present in 33% (39/118) of the patients after a mean disease duration of 5.0±3.3 years. The median SDI score was 1 (range 0-6). Damage to the musculoskeletal system was observed most frequently (9%), followed by neuropsychiatric (7%), ocular (7%), skin (7%), pulmonary (5%) and renal (5%) systems. No malignancies were encountered. Damage was significantly more likely in patients who had experienced neuropsychiatric manifestations during the first year of disease, had major infections or were treated with cyclophosphamide, MMF or rituximab (p<0.05). There was no association of damage with gender, renal involvement or cumulative dose of prednisone. Conclusions: In a large cohort of children with jSLE, damage was common, but less frequent than previously reported. Neuropsychiatric involvement during the first year of disease, major infections and immunosuppressive therapy with cyclophosphamide, MMF and rituximab were identified in this cohort as risk factors for damage. References: Gutiérrez-Suárez R et al. Arthritis Rheum 2006. 54:2989-96. Ravelli A et al. Arthritis Rheum 2003. 49:501-7. Disclosure of Interest: None Declared